Application of Visual Learning Media in Mathematics Learning Class II Fractional Materials at Griya Bandung Indah Public Elementary School - Dinie Anggraeni Dewi; Lara Sati; Juansah Juansah (CV. Rayyan Dwi Bharata, 2023)
Mathematics is one of the subjects that plays an important role at an educational level. In order to increase students' interest or enthusiasm for learning in mathematics, the teacher must create a pleasant learning atmosphere. The main purpose of conducting this research was to see the results of student learning in mathematics, especially fraction material using visual learning media in grade II elementary school. Quantitative method is the method used in this study. The place for this research was SDN Griya Bandung Indah. The subjects in this study were class II A students who had a total of 24 people, namely 11 boys and 13 girls. Based on the analysis of learning outcomes and student responses with fulfilled results, the use of visual learning media in elementary school mathematics class II can be applied.